2015
DOI: 10.1093/nar/gkv870
|View full text |Cite
|
Sign up to set email alerts
|

Structure ofNaegleriaTet-like dioxygenase (NgTet1) in complexes with a reaction intermediate 5-hydroxymethylcytosine DNA

Abstract: The family of ten-eleven translocation (Tet) dioxygenases is widely distributed across the eukaryotic tree of life, from mammals to the amoeboflagellate Naegleria gruberi. Like mammalian Tet proteins, the Naegleria Tet-like protein, NgTet1, acts on 5-methylcytosine (5mC) and generates 5-hydroxymethylcytosine (5hmC), 5-formylcytosine (5fC) and 5-carboxylcytosine (5caC) in three consecutive, Fe(II)- and α-ketoglutarate-dependent oxidation reactions. The two intermediates, 5hmC and 5fC, could be considered either… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
34
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 38 publications
(48 reference statements)
2
34
0
Order By: Relevance
“…T1372A produces 65% fC/caC, while T1372E and T1372V are able to produce only 8% and 3% fC, respectively. When starting with fC substrate under the same conditions, WT enzymes convert about half of fC to caC, corroborating that the final step of oxidation is the least efficient 13,23 . T1372A generates 19% caC, ~1/3 of the WT level, while E/V mutants make <3% caC, near or below the detection limits of our assays.…”
Section: Resultsmentioning
confidence: 54%
See 3 more Smart Citations
“…T1372A produces 65% fC/caC, while T1372E and T1372V are able to produce only 8% and 3% fC, respectively. When starting with fC substrate under the same conditions, WT enzymes convert about half of fC to caC, corroborating that the final step of oxidation is the least efficient 13,23 . T1372A generates 19% caC, ~1/3 of the WT level, while E/V mutants make <3% caC, near or below the detection limits of our assays.…”
Section: Resultsmentioning
confidence: 54%
“…Using a structure-based algorithm 28 recently borne out by crystal structures 23 , we found that Thr1372 and Tyr1902 align with Ala212 and Phe295 in NgTetl, respectively (Supplementary Fig. 1c), making NgTetl analogous to our T1372A/Y1902F double mutant.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…The enzyme interacts almost exclusively with the strand bearing the oxidation target, and it makes hydrogen bonds exclusively with the CpG dinucleotide, with the 5m C/ 5hm C/ 5f C base flipped into the active site to project toward the Fe(II) and αKG. [34][35][36][37] The disposition of the substrate and co-substrate sub-sites may thus dictate that partially oxidized species and DNA dissociate to allow for net replacement of succinate by αKG.…”
mentioning
confidence: 99%